Maternal and perinatal mortality, morbidity and risk factor evaluation in ante partum hemorrhage associated with Placenta Praevia (Bangladesh Critical Care Journal, 2013)
Objective: To determine the maternal & perinatal morbidity and mortality associated with Placenta Praevia in Bangladesh. To assess the risk factors of antepartum hemorrhage associated with Placenta Praevia. Design: A cross sectional observational hospital based descriptive study. Setting: Obstetric inpatient units of two tertiary care teaching hospitals of Dhaka. Participants: One hundred pregnant mothers with diagnosis or Placenta Praevia proven by pelvic ultra sonography presenting with ante partum hemorrhage . Outcome: Incidence of maternal and fetal morbidity and mortality and risk factors of ante partum hemorrhage in Placenta Praevia. Results: 38% study mothers had no ante natal care. There was no maternal death. 96% of mothers were delivered by Caesarean Section. Incidence of primary post partum hemorrhage was 38%. There were 21% still birth and 16% neonatal death. 47% mothers had no complication after delivery. 22% mothers presented with hemorrhagic shock. 59% delivered babies had birth weight below 2.5 kg and 55% delivered babies had no complication. 57% mothers belonged to low socio economic group. Conclusion: The study reflects status of mothers presenting with Placenta Praevia with perinatal morbidity and mortality in a small urban population of Bangladesh treated at two tertiary care hospitals of Dhaka. It is recommended that mothers with Placenta Praevia need to have access to prenatal care and at the same time need to be educated about the benefit of prenatal care. Emergency management of ante partum hemorrhage with hemorrhagic shock should be widely available to improve the outcome of Placenta Praevia in our population. DOI: http://dx.doi.org/10.3329/bccj.v1i2.17197 Bangladesh Crit Care J September 2013; 1 (2): 65-70